ANALISIS KUALITAS PELAYANAN PUBLIK DESA CENGKONG KECAMATAN PURWASARI KABUPATEN KARAWANG - Muhamad Naim Ilyasa; Hanny Purnamasari; Lina Aryani (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
Public services are a fundamental necessity that cannot be separated from the lives of society, from the highest level, namely the central government, to the lowest level, namely the village government. This study aims to examine and analyze the quality of public services in Cengkong Village, Purwasari Subdistrict, Karawang Regency. The method used in this study is qualitative with a case study design, focusing on public services at the village level, which still face many challenges, particularly in Karawang Regency. To assess the quality of public services in Cengkong Village, the researcher applies Edward III’s service quality theory as the analytical framework, which consists of the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. The results of this study indicate that the quality of public services in Cengkong Village can be considered quite good in supporting services provided to the community. However, the quality of public services in Cengkong Village still needs further improvement, particularly in the tangible dimension facilities and infrastructure and the reliability dimension the dependability of Cengkong Village officials.